Buddhist Festivals Throughout the Year - Ganeri, Anita (London Franklin Watts, 2003)
Introduces the main religious festivals of Buddhism, telling the story behind each festival, describing how it is celebrated around the world, and providing instructions for related activities.
Include Colour Illustrations, Glossary and Index
Keywords: Buddhism--Customs and practices -- Fasts and feasts--Buddhism